基于Pro/E的汽车转向梯形机构的设计 - 吕明; 方宗德; 张国胜; 颜克志; 李俭波 (Jixie chuandong)
The design of Ackerman geometry plays a very important role on vehicle design, reasonable design could reduce the slipping in turning, make the abnormal wear in a permissive range. A new method of Ackerman geometry design is discussed based on electric vehicle sample. According to this method, Pro/E is used to establish 3-D solid model and the model is used for motion simulation, data of simulation is collated by MATLAB. Thus, engineers could know whether the design Ackerman geometry is reasonable in time.